The elimination of heavy metals-containing wastewater by adsorption using adsorbent made from Paphia Undulata (“Siput Retak Seribu”): article - Khosim, Noor Amilia; Jafri, Hasnora (2017)
Water is widely used in household area and in industries. In order to keep the clean water supply in line, wastewaters needed to be treated before they can be reuse again. The objectives of this study were to prepare adsorbent made from Paphia Undulata (“Siput Retak Seribu‘) and investigate its effectiveness in removing heavy metals of zinc and iron. The effects of initial adsorbent dosage and contact time were studied. The maximum uptake of zinc ions was obtained at 99% with the dose of 0.75 g and 97% with the dose of 0.50 g for iron. The optimum contact time for zinc and iron to be 99% removed from the synthetic wastewater was in 30 minutes. Both were achieved by using calcined adsorbent at 500°C. The Paphia Undulata could be considered as an effective, low-cost adsorbent to be used for heavy metals removal from wastewater.